UJI PARSIAL CASH RASIO TERHADAP RETURN ON EQUITY PADA PERUSAHAAN RETAIL TRADE, PERUSAHAAN TELEKOMUNIKASI, DAN PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yuniastuti, Rina Milyati (Jurnal Manajemen Magister Darmajaya, 2018)
Independent variable in this research are variable cash ratio and return on equity as dependent variable. This research on three companies is retail trade company, telecomunication company and transportation company. As for the results of the reseach for retail trade company and telecomunication companies have no effect partially on the cash ratio to ROE ( return on equity), and to transportation companies have a partial influence between cash ratio to ROE. In retail trade and telecommunication companies, cash ratio does not affected ROE, because both companies in its operations can use cash ratio with inventory of goods or services. While the transportation company cash ratio affect ROE because of the company should be able to pay off debts term, both long term and short term, that is to take advantage of the advantages over capital in deposit the mainstay of the company of operations.Key word - Cash ratio, Return on Equity, t test/Partial test.